The role of artificial intelligence in financial inclusion in emerging markets: A conceptual review - Ali, Alrsheedi; Iskandar, Yulita Hanum P (Edelweiss Applied Science and Technology, 2025)
Technological advancements have significantly transformed the financial services industry with the increasing implementation of artificial intelligence (AI). Therefore, the rapid growth of AI and its potential to drive financial inclusion, particularly in emerging markets, has highlighted a critical research gap in the conceptual and theoretical frameworks. This gap continues to stifle the effective application of AI in the financial domain. This study is unique because it merges social influence and ethical considerations into the TOE framework and DOI theory to enhance the existing body of knowledge. We propose that technological and organizational readiness, social influence, and ethical considerations are key drivers of AI adoption and promoters of financial inclusion. An integrative review covering the period from 2018 to 2023 and based on the Scopus database, combined with a bibliometric approach, was employed to analyze the growth of the literature, identify leading countries in AI research, and establish key themes and keywords. This study provides a holistic perspective on existing academic studies using the proposed model based on a comprehensive review of the AI and financial inclusion literature. It also identifies key propositions for future research and emphasizes the role of managers and decision-makers in driving AI adoption and supporting societal development.